PENERAPAN TERAPI SELF-DISCLOUSURE PADA REMAJA YANG MENGALAMI STRES - Yani, Sutri; Nilawati, Iin (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2021)
Self-disclosure therapy is stress therapy through self-disclosure, which is the activity of sharing familiar feelings with others through telling stories, communicating deeply, and allowing themselves to be known by others. The ability to express oneself, such as feelings and thoughts, to others is recognized as important. This study aims to determine the effect of self-disclosure therapy on adolescents who experience stress on reducing stress levels. This study used a quasi experimental design. The sample in this study were teenagers, amounting to 29 respondents. In this study, respondents were given a pre-test before being given self-disclosure therapy. Then the respondent is given self-disclosure therapy. After being given therapy, the respondent is given a post test, then the stress level is measured. The results showed that there was an effect of self disclosure on adolescents who experienced stress. This can be seen from the mean stress level before self-disclosure therapy, the mean stress level (24.31) and after the self-disclosure therapy, the mean stress level (16.34). The results of statistical tests using the Man-Wilney test showed that the P value = 0.000, which means that there is a significant effect of providing self-disclosure therapy on reducing stress levels in adolescents who experience stress. It is hoped that self-disclosure therapy can be used as an alternative therapy to reduce stress levels in adolescents.Â Keywords: Self Disclousure; Stress; Adolescencts